2016
DOI: 10.1159/000446340
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in Breast Cancer

Abstract: The importance of the tumor microenvironment including immune cell infiltrates in breast cancer has long been recognized. Tumor-infiltrating lymphocytes are prognostic and predictive; however, their prevalence as well as their prognostic and predictive power are subtype-dependent and appear most prominent in aggressive subtypes like triple-negative and HER2-positive disease. The immune responses observed in many cancers are attracted by tumor-associated antigens and, as suggested by recent research, by neoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…The cancer microenvironment was postulated to modulate immune cell infiltration and immune cell function( 36 , 51 , 52 ). Interestingly, triple negative breast cancer tumors analyzed in this study showed strong correlation between distinct immunosuppressive features.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer microenvironment was postulated to modulate immune cell infiltration and immune cell function( 36 , 51 , 52 ). Interestingly, triple negative breast cancer tumors analyzed in this study showed strong correlation between distinct immunosuppressive features.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its higher genetic instability, an enhanced mutational load, and the appearance of neoantigens PD-L1 expression is more frequently found in HER2-positive and triple negative BCs than in other BC sub-entities (e.g., the luminal cohorts) [ 7 ]. Moreover, PD-L1 expression has been associated with the degree of tumor infiltrating lymphocytes (TILs) [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 36 However, the inability to overcome immune-tolerogenic mechanisms has severely inhibited the development of self-antigen based vaccines, and despite much effort having been put into vaccine trials, their therapeutic efficacy remains disappointing. 41 , 42 Also taking into account data from clinical trials on other self-antigen based vaccines, it can be concluded that neither the use of potent adjuvants nor the introduction of T helper cell epitopes into the self-antigen are sufficient means to enable autoantibody responses with clinical efficacy. 30 Multivalent display ( e.g.…”
Section: Discussionmentioning
confidence: 99%